Prove that:
sec⁴ A (1 - sin⁴ A) - 2tan² A = 1
Answers
Answered by
1
Answer:
here it is
Step-by-step explanation:
sec⁴A(1-sin⁴A)-2tan²A
=sec⁴A-sec⁴Asin⁴A-2tan²A
=sec⁴A-sin⁴A(1/cos⁴A)-2tan²A
=sec⁴A-tan⁴A-2tan²A
={(sec²A)²-(tan²A)²}-2tan²A
=(sec²A+tan²A)(sec²A-tan²A)-2tan²A
=sec²A+tan²A-2tan²A [∵, sec²A-tan²A=1]
=sec²A-tan²A
=1 (Proved)
Answered by
9
Answer:
Here is your answer in the attachment
Mark as brainliest
Attachments:
![](https://hi-static.z-dn.net/files/dde/725d929c6d2f5e8ef9f8a72da95d4e19.jpg)
![](https://hi-static.z-dn.net/files/dbf/d65b1f6b71dc4f0a310ce263c41dba9e.jpg)
Similar questions